Make it personal: Introducing intangible outcomes and psychological sources to flood vulnerability and policy. (May 2021) - Babcicky, Philipp; Seebauer, Sebastian; Thaler, Thomas
Abstract: Vulnerability assessments play a central role in deciding on measures for flood risk reduction. Vulnerability itself manifests as tangible (e.g. building damage) and intangible (e.g. distress, disruption of livelihoods) outcomes caused by a flood event. Traditionally, vulnerability assessments have been focusing on the physical and social sources that drive these outcomes, while psychological sources have largely been neglected. This paper expands the current physical and social perspective on vulnerability by demonstrating the added value of psychological sources to more accurately identify those who are most vulnerable to flooding. Based on survey data of 1127 households living in flood-prone areas in Austria, we confirm that tangible and intangible outcomes represent conceptually distinct types of flood impacts. A series of hierarchical regression models shows that psychological sources do not play a critical role for tangible outcomes, as they do not significantly add to the variance already explained by physical and social indicators. However, psychological sources have substantial unique explanatory value for intangible outcomes, and may supersede certain physical indicators (e.g., risk zone is a physical proxy indicator for the underlying psychological factor 'perceived flood probability'). By contrast, social indicators retain their effect size even if psychological indicators are included. Thus, expanding the scope of vulnerability outcomes calls for simultaneously expanding the scope of sources of vulnerability. The results caution against catch-all risk reducing measures; instead, risk managers should address the vulnerability sources specific to particular outcomes. To improve social equity, flood policy instruments should incorporate intangible outcomes and psychological sources of vulnerability.